The PICHFORK (Pain InCHildren Fentanyl OR Ketamine) trial comparing the efficacy of intranasal ketamine and fentanyl in the relief of moderate to severe pain in children with limb injuries: Study protocol for a randomized controlled trial - Graudins, A.; Meek, R.; Egerton-Warburton, Diana; Seith, R.; Furness, T.; Chapman, Rose (2013)
Background: The effectiveness of intranasal (IN) fentanyl as an analgesic for painful pediatric limb injuries in the Emergency Department (ED) has been reported previously. However, efficacy of IN ketamine in sub-dissociative doses is not well studied in the ED setting. A non-blinded pilot study undertaken by this study group suggested that IN ketamine showed similar analgesic effectiveness to that reported with IN fentanyl in similar non-blinded studies. The aim of this randomized, controlled, equivalence trial is to compare the analgesic effect of sub-dissociative dose IN ketamine with IN fentanyl for children with isolated musculoskeletal limb injuries.Methods/Design: This is a prospective, randomized, controlled, double-blind equivalence trial of children agedthree to thirteen years and less than 50 kg body weight, with isolated musculoskeletal limb injury, presenting to the ED with moderate to severe pain, defined as a verbal response of at least six to a standard 11-point scale (0 = none, 10 = worst pain imaginable). Pain score, sedation, satisfaction with analgesic intervention, and adverse effects will be assessed over a 60 minute interval for each participant. Intranasal ketamine (1 mg/kg) or fentanyl (1.5 microgram/kg) will be administered via blinded syringe and mucosal atomization device in a standardized volume at 0.03 ml/kg, with a maximum volume of 1.5 ml divided equally to both nares. Participants will also receive 10 mg/kg ibuprofen orally. The primary outcome measure will be median change in pain score from pre-administration to 30 minutes post-administration. Non-parametric Mann-Whitney U tests will be computed to compare median change in the primary outcome measure for IN ketamine and fentanyl. A sample size of 36 participants per group is needed to detect the expected 40 mm reduction in pain rating with a 95% confidence interval (CI) no greater than ± 10 mm at 30 minutes. Rescue analgesia will be given as IN fentanyl or intravenous morphine.Discussion: This is the first randomized-controlled trial comparing the efficacy of these two analgesic agents via the intranasal route. If IN ketamine is found to be equally effective to IN fentanyl for this indication, it will provide another analgesic agent that may be considered for the relief of acute pain in children in the ED.Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12612000795897. © 2013 Graudins et al.; licensee BioMed Central Ltd.